The holistic view in forecasting: A conceptual framework to analyze and mitigate cost underestimation arising from optimism bias - Giuseppe Sassano (Project Leadership and Society)
In the intricate landscape of project planning literature, optimism bias emerges as a significant factor influencing estimation inaccuracies. This research delves into the interplay between support and prospect theories, aiming to elucidate the underpinnings of biases in decision-making processes. By juxtaposing these theories within the broader framework of project management, I present an innovative conceptual model that seeks to bridge the gap between the so-called internal and external views in forecasting. This model highlights the potential for a more synergistic approach to forecasting, challenging the traditionally held notion of incompatibility between these perspectives. Through this lens, the author advocates for a holistic approach to project estimation, emphasizing the potential to counteract the pitfalls of cost underestimation stemming from optimism bias. Indeed, by adopting this holistic view, I maintain that project managers and stakeholders can be better equipped to navigate the complexities of project estimation, thereby mitigating the adverse effects of cost underestimation that are intrinsically linked to optimism bias.